Review of Flavor 1 Differences in Meat and Meat Products - Sri Raharjo (Indonesian Food and Nutrition Progress, 1996)
Hundreds or even thousands of volatile compounds present in meat have been documented. However, the flavor of meats have not always been successfully reproduced. This is in part due to interaction of factors such as genetic (species, breed and sex), environment (age, feeding and stress), processing methods (forÂ¬mulation and thermal as well non-thermal processing), chemical and biochemical reactions present in meat. Species as well as type of feed are the most important factors influencing fresh meat flavor, while the flavor of processed meat is mostly determined by product formulation and cooking method.